THE HYDROGEOLOGY AND HYDROGEOCHEMISTRY OF THE BARWON DOWNS GRABEN AQUIFER, SOUTHWESTERN VICTORIA, AUSTRALIA - Petrides B.; Cartwright I. (My University, 2006)
The Barwon Downs Graben lies on the northern flanks of the Otway Ranges and is situated approximately 70 km southwest of Geelong, Victoria, Australia. The major lower Tertiary Barwon Downs Graben aquifer comprises highly permeable sands and gravels interbedded with clays and silts of the hydraulically interconnected Pebble Point, Dilwyn and Mepunga Formations. Groundwater flows east into the Barwon Downs Graben from the Barongarook High, and yields 14C ages up to ~20 ka implying that recharge rates are low and, consequently, that the resource could be impacted by overabstraction. The presence of three different lithological units has led to the development of localized flow systems that has resulted in a lack of regular spatial variations in groundwater chemistry. Stable isotopic data suggests that groundwater was recharged under similar climatic conditions as of today. The major ion chemistry of the freshest groundwater is dominated by Na and HCO3 while higher TDS groundwater, from the confining Narrawaturk Marl, is dominated by Na and Cl. Cl/Br ratios are close to rainfall suggesting that halite dissolution is not the principle source of salts. An excess of Na relative to Cl in fresher groundwater suggests that feldspar dissolution has occurred, however, water–rock interaction is limited. The concentrations of Ca, Mg, and SO4 are controlled by silicate dissolution and ion-exchange reactions with clays.
Keywords: HYDROCHEMISTRY; GROUNDWATER FLOW; ISOTOPES; GROUNDWATER AGE; BARWON DOWNS GRABEN